The Effect of Augmented Reality in Gamification-Based Lessons on Students' Reading Comprehension - Febrian, Dicky Eggy; Dari, Retno Wulan (Journal of English Language and Education, 2025)
This study was carried out to find out the effect of gamified Augmented Reality on the reading comprehension of students at a vocational high school in Indonesia. Since Indonesia performs poorly in PISA reading scores, it adopted AR and gamification as means to enhance attention and understanding. It applied a quasi-experimental design that compared the reading scores of students who learned through gamified AR versus those who received conventional treatment. The participants were 10th-grade students from a public vocational high school in East Java, divided into a control and experimental group. Pre-tests and post-tests were used to measure comprehension. Although the Post-test scores of the experimental group were higher, the difference was not statistically significant. The small effect size implies potential benefits from gamified Augmented Reality on enhancing reading. This study justifies integration of AR into English curricula for richer learning experiences and overcoming challenges in reading within vocational education.